Optical second harmonic generation of V‐shaped chromium nanoholes—dependence on the structure parameters of the nanoholes. (28th July 2014) - Quang, Ngo Khoa; Miyauchi, Yoshihiro; Mizutani, Goro; Charlton, Martin D.; Chen, Ruiqi; Boden, Stuart; Rutt, Harvey; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> We investigated optical second harmonic generation (SHG) from the arrays of V‐shaped chromium nanoholes with the arm width of 50 nm. We systematically investigated the dependence of the SHG intensity on the designed parameters of Cr nanoholes, i.e. the arm length and apex angle. Several combinations of structural parameters of apex angles (A) and arm lengths (L) were examined. The SHG intensity in Pin/Pout configuration was enhanced when L was enlarged. We suggest that the nonlinear optical behavior was dictated by the bulk contribution of metallic electrons. Copyright © 2014 John Wiley & Sons, Ltd.